SPECIFICS OF MARKETING ACTIVITY IN THE PROPERTY MARKET, TO IMPLEMENT INNOVATIVE PROJECTS - Mustafa Malla Osman Shadi (Статистика и экономика, 2016)
The article deals with marketing activities, in terms of project management in the field of real estate and associated works. The specificity of the activities of the developer of combining marketing and design activities at different stages of the innovation project. The main feature of the result of the acts and flexible model for the implementation of project activities, depending on the view of the preferences and expectations of the customer in real estate.